Utilization study of antidiabetes medicines at a tertiary care hospital in Nigeria - Roland Nnaemeka Okoro; Chijioke Nmeka; Patrick O. Erah (SpringerOpen, 2018)
Objectives: To describe antidiabetes medicines prescribing and utilization patterns and to demonstrate gender, and age specific differences in the antidiabetes medicines consumption in the National Health Insurance Scheme (NHIS). Methods: One hundred and fifteen out-patients prescriptions that contained at least one antidiabetes medicine issued to different NHIS patients that attended the health facility in 2013 were used for this study. WHO drug prescribing indicators was used to evaluate the medicines prescribing patterns, while WHO Anatomical Therapeutic Chemical/Defined Daily Dose methodology was used to describe the antidiabetes medicines consumption patterns. Results: The average number of all medicines prescribed per encounter was 5.9 ± 2.0. The percentage of medicines prescribed by generic names and antidiabetes medicines from NHIS essential medicine list were 53.2% and 49.0% respectively. Metformin alone and combinations were most predominantly prescribed, higher proportion of prescriptions comprised multi antidiabetes medicine regime (77.4%) than monotherapy (22.6%). Metformin alone, glibenclamide, and glimepiride made it to Drug utilization 90% segment with an index of adherence to the reference clinical guidelines of 83.6%. Metformin was the most consumed antidiabetes medicine and was equally consumed by both women and men (15.8 vs 15.9 DDD/1000 Patients/Day, p > 0.05). Compared to other age groups, patients aged 40-59 years consumed significantly higher metformin, glibenclamide, and glimepiride than other age groups (p < 0.05). Conclusion: This study shows a tendency for irrational prescribing, metformin was the most prescribed and consumed antidiabetes medicine. No substantial gender difference was observed, but higher consumption of antidiabetes medicines was noted in patients aged 40-59 years than other age groups. Keywords: Antidiabetes medicine, Defined daily dose, Diabetes mellitus, Drug utilization, National Health Insurance Scheme